2019
DOI: 10.46310/tjim.634597
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Hypertension

Abstract: Obesity is an important public health problem with increasing frequency, leading to different comorbidities including hypertension and can cause mortality. Possible mechanisms that increase blood pressure in overweight and obese people are renal damage, activation of the renin-angiotensin-aldosterone system, insulin resistance, hyperinsulinemia, sleep apnea syndrome, leptin-melanocortin pathway and genetic predisposition. Most of these mechanisms stimulate the sympathetic nervous system. Medical nutrition ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 61 publications
0
10
1
Order By: Relevance
“…The risk of hypertension is substantially increased by being overweight and obese. 14 In a study conducted in Osun State, a strong significant relationship was established between body mass index, waist circumference, and blood pressure. 30 This study found a high prevalence of overweight and obesity, a high risk of abdominal obesity, and a high prevalence of prehypertension and hypertension among the respondents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The risk of hypertension is substantially increased by being overweight and obese. 14 In a study conducted in Osun State, a strong significant relationship was established between body mass index, waist circumference, and blood pressure. 30 This study found a high prevalence of overweight and obesity, a high risk of abdominal obesity, and a high prevalence of prehypertension and hypertension among the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Several studies have reported links between overweight, obesity, and hypertension. [12][13][14] According to Saydah et al,12 35.7% of obese individuals had hypertension in the National Health and Nutrition Examination Survey (NHANES) 1999-2010. There is an increase in the frequency of hypertension with a BMI elevated from the lower limit to the upper limit of normal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic mechanism of obesity-related hypertension is not fully understood, but it is likely that multiple pathogenetic mechanisms may contribute to the development of higher BP in obese individuals [6,15]. Moreover, obesity-related hypertension is nothing but a relation between high blood pressure and BMI, which is also used as indicator of underweight (BMI= < 18.5 kg/m) due to chronic energy deficiency or low body fat percentage [8].…”
Section: Introductionmentioning
confidence: 99%